2020
DOI: 10.3390/w12123336
|View full text |Cite
|
Sign up to set email alerts
|

Deficit Irrigation as a Suitable Strategy to Enhance the Nutritional Composition of HydroSOS Almonds

Abstract: The Mediterranean region is one of the most water-scarce areas worldwide and is considered a climate-change hotspot. To assure the viability and competitiveness of irrigated agriculture, it is vital to implement strategies that can maximize water saving without compromising yield. Deficit irrigation (DI) for cultivating drought-tolerant species such as almond (Prunus dulcis (Mill.) D.A. Webb) can help in achieving this goal, while at the same time improving fruit chemical composition. This work evaluated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…The main organic acids found were citric, tartaric, malic and isobutyric. All these OA had been previously found in raw almonds except for isobutyric acid (Egea et al, 2009;Lipan et al, 2020). Citric acid was higher in T2 (2.5 g kg -1 ) than T1 (2.3 g kg -1 ) and the contrary was observed for the isobutyric acid and total organic acids content (∑OA).…”
Section: Organic Acids and Sugarsmentioning
confidence: 65%
See 1 more Smart Citation
“…The main organic acids found were citric, tartaric, malic and isobutyric. All these OA had been previously found in raw almonds except for isobutyric acid (Egea et al, 2009;Lipan et al, 2020). Citric acid was higher in T2 (2.5 g kg -1 ) than T1 (2.3 g kg -1 ) and the contrary was observed for the isobutyric acid and total organic acids content (∑OA).…”
Section: Organic Acids and Sugarsmentioning
confidence: 65%
“…Similar results were reported in previous studies in which an increase in all OA, was observed in almonds cvs. Marta, Guara, and Lauranne grown both under RDI or sustained deficit irrigation (SDI) (Lipan et al, 2020;Gutiérrez-Gordillo et al, 2020). Regarding the roasting process, citric, isobutyric and ∑OA increased 1.18-fold, 2.58-fold, (from 150 to 190 ºC) and 1.03-fold (from 150 ºC to 190 ºC) respectively, with the roasting temperature.…”
Section: Organic Acids and Sugarsmentioning
confidence: 99%
“…They observed significant differences in the response of these cultivars, detecting an increase in the contents of sugars and fatty acids in the almonds from the SDI treatments, without relevant yield losses. These authors found highly significant correlations between leaf water potential (an indicator of tree water status) and fumaric acid, sugars, and fatty acids in the almonds [5]. This work opens the way to defining irrigation protocols adapted to specific almond cultivars and that account for both production and the nutritional composition of almonds.…”
Section: Overview Of This Special Issuementioning
confidence: 80%
“…The efficient use of deficit irrigation strategies is the subject of two articles within this Special Issue. First, Gutiérrez-Gordillo et al [5] tested two sustained deficit irrigation (SDI) regimes, varying the dose of water applied, against a full irrigation control in three almond cultivars grown in South Spain. They observed significant differences in the response of these cultivars, detecting an increase in the contents of sugars and fatty acids in the almonds from the SDI treatments, without relevant yield losses.…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…• In almond orchards, regulated deficit irrigation strategies and subsurface drip irrigation have allowed a 45% water saving while production was reduced by 17% [45]; deficit irrigation has improved almond quality and water saving, without significant yield loss [46]. A crucial requirement to perform LCA and LCC is the availability of complete and accurate technical and economic data-set regarding the whole cultural cycle.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%